Identification and measurement of brand identity and image gap: a quantitative approach. Issue 3 (13th May 2014) - Roy, Dilip; Banerjee, Saikat
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to offer a quantitative methodology to identify and measure the gap between the communicated brand identity and perceived brand image by channel members and the consumers. Brand marketers communicate with their target consumers to make them aware of brand identity and communicate the same way to the channel members directly. Channel members, in turn, convey the same to the end-users. Thus, a proper alignment of these three crucial nodes, namely, brand marketers, channel members and consumers, is inevitable for the efficient transfer of brand identity. However, in reality, not all are successful to synchronize communicated brand identity and image perception. So, the identification and measurement of identity-image gap is essential. Design/methodology/approach – Based on the literature review, the authors propose a conceptual model for the study and generate the basic research questions. In this study, Kapferer's brand identity prism has been taken as the focal point of study to measure brand identity. So far as the vector measure is concerned, a p-dimensional setup is present, each dimension representing each facet of Kapferer's brand identity prism. Now, given these sets of observations, the authors introduce for each set, a multivariate distributional setup to represent the underlying population behavior. Findings – In this study, a theoretical framework is proposed to identify and measure brand identity and image consistency. To minimize the problem associated with subjective decisions, an objective procedure has been proposed to measure the brand knowledge structure of company personnel, consumers and channel members about the considered brands. The results of this study show that brand knowledge consistency is missing among marketers, consumers and channel members for considered brands. The proposed methodology may help marketers to measure the identity-image gap in a more objective manner with pinpoint accuracy by adopting a quantitative approach. Practical implications – The proposed methodology may help marketers to measure the identity-image gap in a more objective manner with pinpoint accuracy by adopting a quantitative approach. Once a gap is identified, it will be easy for marketers to adopt possible measures to bridge the gap. This helps brand marketers to understand the branding process more objectively. Originality/value – To the best of the authors' knowledge, there is a lack of concrete quantitative approach, attempting to discuss the methodology to measure the gap between brand identity facets and brand image. In this backdrop, this might be the first paper offering a quantitative methodology to identify and measure the gap between the communicated brand identity and perceived brand image by channel members and the consumers.